Snake Venom and its Effects on Animal Health - Palasamudram, Dhruv; Ninan, Jacob (International Journal of Bio-resource and Stress Management, 2025)
This review is based on snake venom, and aims at interspersing theory with a practical approach. Snakes have evolved a toxic concoction called venom or zootoxin which has helped them subdue and digest their prey, prior to ingestion. The first signs of venom in snakes date back to 28 million years ago. It was found to be composed of 90% water, lipids, proteins, amino acids, nucleosides, neurotransmitters, and carbohydrates. The various components of snake venom acted on different physiological systems within the victim’s body, eventually subduing them and enabling the snake to consume its meal. Out of the 4,000 described species in the world, about 600 were believed to be venomous, and around 200 of them could cause life threatening symptoms in animals and humans. Following a bite from a venomous snake, first aid must be performed promptly and the individual must be rushed to a nearby hospital to increase their chances of survival. Based on the mode of action of the venom, it is classified into neurotoxic, hemotoxic, cytotoxic and myotoxic. India, home to the 'Big Four' comprising the Russell's viper, Saw-scaled viper, Spectacled cobra and Common krait, which are responsible for the majority of the 58,000 deaths that occured annually as a result of snake envenomation. All the photos used in this article were collected from professionals in the field of herpetology. Some of the information came from actual practitioners who were interviewed either in person or via email.